Double-Serine Fluoroquinolone Resistance Mutations Advance Major International Clones and Lineages of Various Multi-Drug Resistant Bacteria - Fuzi, Miklos; Szabo, Dora; Csercsik, Rita (Frontiers in Microbiology, 2017)
The major international sequence types/lineages of methicillin-resistant Staphylococcus aureus (MRSA), extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae and ESBL-producing E. coli were demonstrated to have been advanced by favorable fitness balance associated with high-level resistance to fluoroquinolones. The paper shows that favorable fitness in the major STs/lineages of these pathogens was principally attained by the capacity of evolving mutations in the fluoroquinolone-binding serine residues of both the DNA gyrase and topoisomerase IV enzymes. The available information on fitness balance incurred by individual and various combinations of mutations in the enzymes is reviewed in multiple species. Moreover, strong circumstantial evidence is presented that major STs/lineages of other multi-drug resistant bacteria, primarily vancomycin-resistant Enterococcus faecium, emerged by a similar mechanism. The reason(s) why the major ST/lineage strains of various pathogens proved more adept at evolving favorable mutations than most isolates of the same species remains to be elucidated.